Evaluation Techniques in Medical Education: An Opinion - Attaullah Khan Niazi, Muhammad Muneeb, Muhammad Bilal Moeen-Ud-Din, Sadia Zaheer, Muhammad Mohsin Mahmood, Mohammed Ali, Salik Ahmed Cheema, Yasir Rana, Benazeer Makrani, Saman Qadeer (Pakistan Journal of Medical & Health Sciences, 2024)
Evaluation techniques play a crucial role in medical education at the undergraduate level. Medical educators have been exploring various evaluation techniques to ensure the comprehensive assessment of undergraduate medical students. In this article, we will delve into a comprehensive review and analysis of the existing evaluation methods used in medical education at the undergraduate level. By understanding the strengths and limitations of these techniques, educators and administrators can make informed decisions about the most effective evaluation methods for their institutions. Moreover, this review will provide valuable insights for future research and development in the field of medical education evaluation. To conduct a comprehensive review and analysis of evaluation techniques in medical education at the undergraduate level, a thorough literature review was conducted. The review included a wide range of sources such as academic journals, textbooks, and reports from reputable medical education organizations. Key evaluation methods were identified and analyzed based on their usage, effectiveness, and applicability to the undergraduate medical curriculum. Additionally, specific criteria such as validity, reliability, feasibility, and acceptability were considered in evaluating the effectiveness of these techniques. Furthermore, a comparative analysis of the identified evaluation techniques was performed, considering factors such as validity, reliability, feasibility, and acceptability among educators and students. This allowed for a deeper understanding of the strengths and limitations of each method, providing valuable insights into their practical implementation and impact on student learning outcomes. Keywords: Evaluation techniques, medical education, applications, multiple choice question.